2019
DOI: 10.3390/ijms20174088
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Novel Metalloproteinase from Agkistrodon Venom and Its Antithrombotic Activity Analysis

Abstract: Snake venom contains large amounts of active proteins and peptides. In this study, a novel snake protein, metalloproteinase SP, was successfully isolated from the venom of Agkistrodon acutus by multi-gel chromatography. The isolated protein exhibits anti-platelet aggregation activity. Animal experiments showed that it exhibited defibration, anticoagulation, and antithrombotic effects and contributes to improved blood rheology and antiplatelet aggregation. In vivo experiments demonstrated that it prolonged clot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Metalloproteinases inhibit platelet aggregation, caused by inducers, such as ADP and collagen, and reduce platelet adhesion. Metalloproteinases can decompose fibrinogen, reduce fibrinogen content, and regulate the formation of thrombus and the spatial structure of a thrombus [ 18 , 40 ]. Some metalloproteinases play a thrombolytic effect by directly decomposing fibrin in the thrombus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metalloproteinases inhibit platelet aggregation, caused by inducers, such as ADP and collagen, and reduce platelet adhesion. Metalloproteinases can decompose fibrinogen, reduce fibrinogen content, and regulate the formation of thrombus and the spatial structure of a thrombus [ 18 , 40 ]. Some metalloproteinases play a thrombolytic effect by directly decomposing fibrin in the thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the venom comprised 84 distinct proteins from 10 toxin families and 12 other proteins. The whole venom or some of the purified components of the Deinagkistrodon acutus venom have been subjected to biochemical and pharmacological characterization, such as MSP, Pt-A (Glu-Asn-Trp), SLPC, ACH-11 [ 16 , 17 , 18 , 19 ]. However, the protein compositions of Deinagkistrodon acutus ’s venom in different regions may be different [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The content of this Special Issue highlights the multiple biological functions of these proteolytic enzymes and includes four review articles [4,[15][16][17] and 10 original articles [18][19][20][21][22][23][24][25][26][27]. The articles address the role of MMPs, ADAMs, and ADAMTSs, in normal physiology as well as in neoplastic and tissue destructive processes.…”
mentioning
confidence: 99%
“…While they are beneficial for normal anastomotic wound healing [9,48], broad-spectrum MMPI therapies are detrimental to anastomotic wound repair under Snake venom metalloproteinases belong to the adamlysins, and their antithrombotic effects are well-known [32]. Huang et al [21] tested the therapeutic effect of the metalloproteinase SP, which was isolated and purified from the venom of a moccasin snake (Agkistrodon acutus), in animal models of induced thrombosis and pulmonary embolism. The protein prolonged the coagulation time and inhibited platelet aggregation and thrombosis.…”
mentioning
confidence: 99%